Nuclear factor‐kappa B‐dependent X‐box binding protein 1 signalling promotes the proliferation of nucleus pulposus cells under tumour necrosis factor alpha stimulation. (14th November 2018) - Chen, Lu; Xie, Zhi‐Yang; Liu, Lei; Zhu, Lei; Wang, Feng; Fan, Pan; Sinkemani, Arjun; Zhang, Cong; Hong, Xin; Wu, Xiao‐Tao
Abstract: Objectives: Tumour necrosis factor alpha (TNF‐α) expressed by nucleus pulposus cells (NPCs) plays a critical role in intervertebral disc (IVD) degeneration. A key unfolded protein response (UPR) component, X‐box binding protein 1 (XBP1) and nuclear factor‐kappa B (NF‐κB) are essential for cell survival and proliferation. The aim of our study was to elucidate the roles of XBP1 and NF‐κB in IVD degeneration (IDD). Materials and methods: Rat NPCs were cultured with TNF‐α in the presence or absence of XBP1 and NF‐κB‐p65 small interfering RNA. The associated genes and proteins were evaluated through quantitative real‐time PCR, Western blot analyses and immunofluorescence staining to monitor UPR and NF‐κB signalling and identify the regulatory mechanism of p65 by XBP1. Cell counting kit‐8 assay, cell cycle analysis and related gene and protein expression were performed to examine the proliferation of NPCs. Results: The acute exposure of TNF‐α accelerated the proliferation of rat NPCs by activating the UPR/XBP1 pathway. XBP1 signalling favoured the phosphorylation and nuclear translocation of p65 subunit of NF‐κB. The activation of NF‐κB in the later phase also enhanced NPC proliferation. Conclusions: Unfolded protein response reinforces the survival and proliferation of NPCs under TNF‐α stimulation by activating the XBP1 pathway, and NF‐κB serves as a vital mediator in these events. The XBP1 signalling of UPR can be a novel therapeutic target in IDD.